2019
DOI: 10.1049/el.2019.2415
|View full text |Cite
|
Sign up to set email alerts
|

Current mirror‐based compensation circuit for multi‐row read in‐memory computing

Abstract: Multi‐row read plays an important role in in‐memory computing and its precision affects the accuracy of the calculation. In this brief Letter, a discharge compensation method is proposed for the linearisation of multi‐row read operations in static RAM. Current mirrors are added to bitlines to compensate for the discharge voltage. With compensation, the integral non‐linearity decreases by 72% compared with the situation without compensation. In addition, a wordline signal generation circuit based on replica bit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(13 reference statements)
0
0
0
Order By: Relevance
“…where LSB is the least significant bit-the ideal unit of change between two adjacent results. We tally the INL of our results and the results of [12,13] in Figure 5, which are all under tt corner conditions and 25 • C The INL of our results was calculated using the data for the calculated ideal line as the Ideal Value and the average result voltage of all possible calculation combinations as the Tested Value. The INL from [13] are under the conditions of VDD = 0.8 V and Last Column in their article, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…where LSB is the least significant bit-the ideal unit of change between two adjacent results. We tally the INL of our results and the results of [12,13] in Figure 5, which are all under tt corner conditions and 25 • C The INL of our results was calculated using the data for the calculated ideal line as the Ideal Value and the average result voltage of all possible calculation combinations as the Tested Value. The INL from [13] are under the conditions of VDD = 0.8 V and Last Column in their article, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, they increase the amount of data transferred on-and off-chip, which contrasts with the fundamental targets of CIM, so on-chip solutions are fairly proposed. Related works that have used on-chip circuit methods are as follows: Z. Lin in [12] proposed a current-mirrorbased compensation circuit which provided an extra charge current for the bitline when the voltage is low. In [13], they improved their design by separating the capacitance and the bitline with a cascade current mirror.…”
Section: Recent Techniquesmentioning
confidence: 99%
“…However, when the signal margin is less than the input offset of the analog readout circuit, the sensing amplifier (SA) or the ADC, the accuracy of the analog readout operation, decreases, resulting in reduced system-level calculation accuracy. Recently, several studies [4][5][6] identified this problem in the SRAM design and, therefore, designed multiple methods to alleviate non-linear current accumulation. For example, in [5], a current mirror is added to improve the linearity by accelerating the BL discharge in the triode region.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies [4][5][6] identified this problem in the SRAM design and, therefore, designed multiple methods to alleviate non-linear current accumulation. For example, in [5], a current mirror is added to improve the linearity by accelerating the BL discharge in the triode region. However, excessive discharge operations may occur with overcompensation or read breaking.…”
Section: Introductionmentioning
confidence: 99%